Permeability variation of sandstone under different water pressures after unidirectional heating. Issue 1 (August 2021) - Xin, Lin; Han, Limin; Feng, Mingze; Li, Kaixuan; Wu, Jing; Li, Jiaze
Abstract: In the process of Underground Coal Gasification (UCG), the permeability of rock around coal seam will change after high temperature. In order to investigate the influence of UCG and groundwater level change on groundwater seepage, an experimental study on permeability change of sandstone under unidirectional heating under different water pressures was carried out. Taking unidirectional heating sandstone as the research object, confining pressure, axial pressure and different water pressure are set to simulate different water pressure environment, and permeability changes are obtained through experiments. The results show that: water pressure has an effect on the permeability of S01, but the permeability does not increase with the increase of water pressure. Under certain stress conditions, there is such a region in S01. When the water pressure is in the region, it has little or even negative effect on the improvement of rock permeability. When the water pressure is not in the region, it has significant effect on the improvement of rock permeability. Through the fitting of permeability and water pressure, it is concluded that the permeability of S07 increases linearly with water pressure, and the permeability of S05 increases nonlinearly with water pressure.